2019
DOI: 10.3390/pharmacy7030108
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of a Practice-Based Network of Pharmacists Working in Family Medicine Groups (FMG)

Abstract: A needs assessment study of pharmacists working in family medicine groups (FMG) demonstrated the necessity to build a practice-based network. This network would foster a faster integration into FMG and a more efficient collaborative practice. It would also take advantage of an existing practice-based research network (PBRN)—the STAT (Soutien Technologique pour l’Application et le Transfert des pratiques novatrices en pharmacie) network. A working group of nine FMG pharmacists from the different regions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The reason for this lack of intraprofessional collaboration (mostly from community pharmacists to FMG pharmacists) could be that community pharmacists have little knowledge of the FMG in which a pharmacist is practising. One of the first tools developed by the practice‐based network is a directory of all FMG pharmacists with their contact information in the FMG . Better intraprofessional collaboration could improve continuity of care, cut short the duplication of care and facilitate the transfer of activities that can be performed in community pharmacies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reason for this lack of intraprofessional collaboration (mostly from community pharmacists to FMG pharmacists) could be that community pharmacists have little knowledge of the FMG in which a pharmacist is practising. One of the first tools developed by the practice‐based network is a directory of all FMG pharmacists with their contact information in the FMG . Better intraprofessional collaboration could improve continuity of care, cut short the duplication of care and facilitate the transfer of activities that can be performed in community pharmacies.…”
Section: Resultsmentioning
confidence: 99%
“…Hazen et al also observed that formal training days with peers were highly valued to counterbalance the lack of a role model in the workplace. The practice‐based network will develop a mentorship programme to better support pharmacists and to increase their confidence in their capacity to play their role optimally . Tools to communicate pharmacists' competencies to other team members and to promote the role of pharmacists in the FMG are under development.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations